2019
DOI: 10.1016/j.niox.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic high-dose beetroot juice supplementation improves time trial performance of well-trained cyclists in normoxia and hypoxia

Abstract: Chronic high-dose beetroot juice supplementation improves time trial performance of well-trained cyclists in normoxia and hypoxia, Nitric Oxide (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 67 publications
7
45
0
Order By: Relevance
“…Previous studies have shown this level of consumption sufficient to increase NO 2 levels and improve exercise performance in younger highly trained athletes [13] and younger recreationally active men [5]. Following consumption of the high NO 3 beverage, plasma NO 3 and NO 2 levels were increased by 934 and 428 percent, respectively, similar to previously reported finding in both younger [15] and older adults [24].…”
Section: Effects Of Dietary Nitrate Supplementation On Plasma Nitritesupporting
confidence: 84%
See 3 more Smart Citations
“…Previous studies have shown this level of consumption sufficient to increase NO 2 levels and improve exercise performance in younger highly trained athletes [13] and younger recreationally active men [5]. Following consumption of the high NO 3 beverage, plasma NO 3 and NO 2 levels were increased by 934 and 428 percent, respectively, similar to previously reported finding in both younger [15] and older adults [24].…”
Section: Effects Of Dietary Nitrate Supplementation On Plasma Nitritesupporting
confidence: 84%
“…These results would suggest that an improvement in exercise economy was not the mechanism responsible for the increase in exercise duration noted in some of our subjects. Rokkendal-Lausch et al reported similar findings in their young well-trained cyclists [15]. They found that while NO 3 supplementation did improve time trial performance, it had no effect on exercise economy as measured by the power output to V O 2 ratio.…”
Section: Exercise Economymentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, found that TT performance and power output improved after BRJ supplementation compared to placebo supplementation (7). Also Rokkedal-Lausch et al (2019) found an increase TT performance in hypoxia and normoxia after BRJ consumption (Rokkedal-Lausch et al 2019). Additionally, a study from McQuillan et al (2017) showed beneficial effects on a 4k-TT in well-trained cyclists (McQuillan et al 2017b).…”
Section: Well-trained Menmentioning
confidence: 96%